Kemampuan Pemahaman Konsep Matematis Siswa SMA/MA Melalui Penerapan Model Pembelajaran Learning Cycle 5E - Fadhilah Ammar, Nurul; Khairina; Hafriani (Jumper: Journal of Educational Multidisciplinary Research, 2024)
The ability to understand mathematical concepts is an important asset that students must have in mastering mathematics learning. However, in reality students' ability to understand mathematical concepts is still subdued. So an effort is needed to improve students' ability to understand mathematical concepts by applying a learning model, namely the 5e learning cycle learning model. The aim of this research is to determine the comparison of students' ability to understand mathematical concepts taught using the 5E learning cycle learning model with the ability to understand mathematical concepts of students taught using conventional learning. The research used is quantitative research. The type of research used is quasi-experimental with the research design being a pretest-posttest control group design. The population in this study were all students of  X class MAN 4 Aceh Besar. Sampling in this study used a random sampling technique where the sample consisted of two classes, namely class X.3 as the experimental class and class X.5 as the control class. data collection using pretest-posttest question sheets. The results of data processing using right-hand t-test statistics, obtained  and  Because    then accept  and reject . So it can be concluded that the ability to understand mathematical concepts of students taught using the 5E learning cycle learning model is better than the ability to understand mathematical concepts of students taught using conventional learning.